Answer:
![\frac{1}{2} 3 \\](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7B2%7D%203%20%5C%5C%20%20)
Step-by-step explanation:
Your welcome
Answer:
72°
Step-by-step explanation:
180-3x=2x
5x=180
x=36
Angle CBE = 2(36) = 72
<span>Nadine mixes a juice solution that is made from 3 gallons of an 80% juice solution and 1 gallon of a 20% juice solution. What is the percent concentration of the final solution? =</span>65%
Pick 2 pairs of equations t<span>hen use addition and subtraction to eliminate </span>the same variable<span> from both pairs of equations then it is left with 2 variables
</span>Pick two pairs
<span><span>4x - 3y + z = - 10</span><span>2x + y + 3z = 0
</span></span>eliminate the same variable from each system
<span><span>4x - 3y + z = - 10</span>
<span>2x + y + 3z = 0</span>
<span>4x - 3y + z = - 10</span>
<span>-4x - 2y - 6z = 0</span>
<span>-5y - 5z = - 10</span>
<span>2x + y + 3z = 0</span>
<span>- x + 2y - 5z = 17</span>
<span>2x + y + 3z = 0</span>
<span>-2x + 4y - 10z = 34</span>
<span>5y - 7z = 34
</span></span>Solve the system of the two new equations:
<span><span>-5y - 5z = - 10</span>
<span>5y - 7z = 34</span>
<span>-12z = 24</span>
which is , <span>z = - 2</span>
<span>-5y - 5(- 2) = - 10</span>
<span>-5y = - 20</span>
wich is , <span>y = 4
</span></span>substitute into one of the original equations
<span>- x + 2y - 5z = 17</span>
<span>- x + 2(4) - 5(- 2) = 17</span>
<span>- x + 18 = 17</span>
<span>- x = - 1</span>
<span>x = 1</span>
<span>which is , </span><span>(x, y, z) = (1, 4, - 2)</span><span>
</span>Does 2(1) + 4 + 3(- 2) = 0<span> ? Yes</span><span>
</span>
Answer:
i dunno
Step-by-step explanation:
Im a middle schooler lol